If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6y + 5)(y + -2) = 0 Reorder the terms: (5 + 6y)(y + -2) = 0 Reorder the terms: (5 + 6y)(-2 + y) = 0 Multiply (5 + 6y) * (-2 + y) (5(-2 + y) + 6y * (-2 + y)) = 0 ((-2 * 5 + y * 5) + 6y * (-2 + y)) = 0 ((-10 + 5y) + 6y * (-2 + y)) = 0 (-10 + 5y + (-2 * 6y + y * 6y)) = 0 (-10 + 5y + (-12y + 6y2)) = 0 Combine like terms: 5y + -12y = -7y (-10 + -7y + 6y2) = 0 Solving -10 + -7y + 6y2 = 0 Solving for variable 'y'. Factor a trinomial. (-5 + -6y)(2 + -1y) = 0Subproblem 1
Set the factor '(-5 + -6y)' equal to zero and attempt to solve: Simplifying -5 + -6y = 0 Solving -5 + -6y = 0 Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -6y = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -6y = 0 + 5 -6y = 0 + 5 Combine like terms: 0 + 5 = 5 -6y = 5 Divide each side by '-6'. y = -0.8333333333 Simplifying y = -0.8333333333Subproblem 2
Set the factor '(2 + -1y)' equal to zero and attempt to solve: Simplifying 2 + -1y = 0 Solving 2 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1y = 0 + -2 -1y = 0 + -2 Combine like terms: 0 + -2 = -2 -1y = -2 Divide each side by '-1'. y = 2 Simplifying y = 2Solution
y = {-0.8333333333, 2}
| 13x+7=6x+14 | | -3+7q=-7+9q | | -(1+6m)+6m=-11+3(r-7) | | Y=(5t^2)*(5t^3) | | -2(3)(-5)= | | 3(7-4x)=-39 | | 12=96 | | 3x+3+55=180 | | 4(5x-7)=52 | | 4x^3-34x^2+70x-25=0 | | -5s-9=-2s | | 2x^2-12x=32x-192 | | 3(-7+7x)=168 | | 5(8-8x^2)=8 | | 6y-28=4y-12 | | -7u=-8u+6 | | f(x)=ln(x+1) | | 12x+36=-3x-81 | | -6-5x=4x-51 | | -5+2x-8x+4x=40 | | 5x-(3x-(13-2x))=(6x-14)-189 | | 10+6x=15-7x | | -3-7v=-6v | | 2b+16=-6+4 | | 7x+9=5x+31 | | 2b-12=19b-15 | | 3-8x+3x+5=31 | | 8x+10=15-9 | | P^2=8p | | 3lnx-5lnx=3 | | 5+7x+3x=75 | | 4g-20=9g |